PENGARUH KUALITAS SUMBER DAYA MANUSIA, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH DENGAN SISTEM PENGENDALIAN INTERN PEMERINTAH SEBAGAI VARIABEL INT - Shylvia Andriani; Junaidi; Sri Rahayu (Jurnal Akuntansi & Keuangan Unja, 2016)
The purpose of this research is to determine and obtains evidence empirical about the influence of the quality of human resources, the implementation of the regional financial accounting, and utilization of information technology on the quality of financial reports SKPD with a system of internal control the government as variable intervening. The research on the entire financial administration officials SKPD of Merangin regency on 2016 , by using the primary data was obtained from questionnaires distributed to respondents. A method of the sample collection by using purposive techniques of sampling , as many as 30 respondents. Analysis of data using smartpls version 3.0. through outer, inner model and hypothesis testing. Outer model and inner model showed the results of all research instrument are valid, realiabel and feasible to be to explain a model variables. The results of testing showing directly that the quality of human resources and the utilization of technology not significant on the quality of financial report, regional financial accounting system significant on the quality of financial report. Testing indirectly shows that the quality of human resources, regional financial accounting system, and utilization of information technology not significant on the quality of financial statements with internal control system of government as a variable no intervening. Implication from the review is expected to contribute empirically as lessons learned about the quality of human resources ,the system implementation accounting regional financial, utilization of information technology and system internal control the government in working units. Can also become as a reference for future researches and as information and consideration in the policies on regional financial management to achieve the quality of local government financial statements.